Functional Bowel Complaints and the Impact on Quality of Life After Colorectal Cancer Surgery in the Elderly - Ketelaers, Stijn H. J.; van Heinsbergen, Maarten; Orsini, Ricardo G.; Vogelaar, F. Jeroen; Konsten, Joop L. M.; Nieuwenhuijzen, Grard A. P.; Rutten, Harm J. T.; Burger, Jacobus W. A.; Bloemen, Johanne G. (Frontiers in Oncology, 2022)
Background: The Low Anterior Resection Syndrome (LARS) is commonly reported after colorectal cancer surgery and significantly impairs quality of life. The prevalence and impact of LARS in the elderly after rectal cancer as well as colon cancer surgery is unclear. We aimed to describe the prevalence of LARS complaints and the impact on quality of life in the elderly after colorectal cancer surgery. Materials and Methods: Patients were included from seven Dutch hospitals if they were at least one year after colorectal cancer surgery between 2008 and 2015. Functional bowel complaints were assessed by the LARS score. Quality of life was assessed by the EORTC QLQ-C30 and QLQ-CR29 questionnaires. Outcomes in patients ≥70 years were compared to a reference group of patients <70 years. Results: In total 440 rectal cancer and 1183 colon cancer patients were eligible for analyses, of whom 133 (30.2%) rectal and 536 (45.3%) colon cancer patients were ≥70 years. Major LARS was reported by 40.6% of rectal cancer and 22.2% of colon cancer patients ≥70 years. In comparison, patients <70 years reported major LARS in 57.3% of patients after rectal cancer surgery (p=0.001) and in 20.4% of patients after colon cancer surgery (p=0.41). Age ≥70 years was independently associated with reduced rates of major LARS after rectal cancer surgery (OR 0.63, p=0.04). Patients with major LARS reported significantly impaired quality of life on almost all domains. Conclusion: Elderly should not be withheld a restorative colorectal cancer resection based on age alone. However, a substantial part of the elderly colorectal cancer patients develops major LARS after surgery, which often severely impairs quality of life. Since elderly frequently consider quality of life and functional outcomes as one of the most important outcomes after treatment, major LARS and its impact on quality of life should be incorporated in the decision-making process.